The Effect Of Retailing Mix On Costumer Purchase Decision - Edy Nurtanto; Ermina Rusilawati; Zulfadli Hamzah; Md Zohurul Anis (Yayasan Riset dan Pengembangan Intelektual, 2022)
The pupose of this research was to find out the influence of price, merchandise assortment, communication mix, location, customer service, and store design and display on purchasing decisions at the supermarket CG Mart. The population that becomes the object of this research is all consumers of CG Mart supermarkets. The number of samples used in this study were 100 respondents. The method of analysis used in this study is multiple regression analysis. The results of the study partially show that price has a significant effect on purchasing decisions, merchandise assortment has a significant effect on purchasing decisions, communication mix has effect but not significant on purchasing decisions, location has effect but not significant on purchasing decisions, customer service has a significant effect on purchasing decisions. , the store design and display does have a effect but not significant on purchasing decisions. And the simultaneous research on price, merchandise assortment, communication mix, location, customer service, and store design and display have a significant influence on purchasing decisions at the supermarket CG Mart. Keywords: Price, merchandise assortment, communication mix, location, customer service, store design and display, purchasing decision.